2011
DOI: 10.1016/j.ejpain.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Transdural motor cortex stimulation reverses neuropathic pain in rats: A profile of neuronal activation

Abstract: Motor cortex stimulation (MCS) has been used to treat patients with neuropathic pain resistant to other therapeutic approaches; however, the mechanisms of pain control by MCS are still not clearly understood. We have demonstrated that MCS increases the nociceptive threshold of naive conscious rats, with opioid participation. In the present study, the effect of transdural MCS on neuropathic pain in rats subjected to chronic constriction injury of the sciatic nerve was investigated. In addition, the pattern of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
51
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 79 publications
13
51
1
6
Order By: Relevance
“…We observed a significant association between burning (superficial) spontaneous pain relief and effective results (based on the VAS score) in our study; thus, we believe that the pain relief mediated by MCS is the result of orthodromic activation of the corticofugal pathways and antidromic activation of thalamocortical pathways, and the substantia gelatinosa, which participates in the modulation of the whole pain and the burning pain, plays an important role in these procedures. This is consistent with Fonoff’s research in animal models [26-28]. There are some limitations in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed a significant association between burning (superficial) spontaneous pain relief and effective results (based on the VAS score) in our study; thus, we believe that the pain relief mediated by MCS is the result of orthodromic activation of the corticofugal pathways and antidromic activation of thalamocortical pathways, and the substantia gelatinosa, which participates in the modulation of the whole pain and the burning pain, plays an important role in these procedures. This is consistent with Fonoff’s research in animal models [26-28]. There are some limitations in our study.…”
Section: Discussionsupporting
confidence: 93%
“…According to a study by Goto et al [25] using diffusion tensor imaging to examine the effectiveness of M1 rTMS for CPSP, preservation of thalamocortical and corticofugal motor tracts predicts treatment efficacy. In an animal model of neuropathic pain, Pagano et al [26] and Fonoff et al [27, 28] found that animals treated with MCS had a decrease in Fos and zif expression in the dorsal horn of the spinal cord (DHSC), and an increase in Fos and zif expression in the periaqueductal gray matter. The periaqueductal gray matter is a part of a descending pain suppressor pathway that projects to the DHSC via the rostral ventromedial medulla.…”
Section: Discussionmentioning
confidence: 99%
“…EMCS is thought to revert neuropathic pain phenomena through activation of the limbic and descending pain inhibitory systems, similar to that reported in experimental animals. 95 Implanted MCS seems to have an interesting potential with greater long-term efficacy, but larger comparative and controlled versus placebo clinical studies are required to confirm and validate previously published results. Moreover, further investigation of the mechanisms involved in this effect may improve the clinical treatment of persistent pain.…”
Section: Discussion and Future Directionmentioning
confidence: 95%
“…Dopamine and serotonin can attenuate neuropathic pain, ultimately suppressing the input signal evoked by painful stimulation. [12][13][14]28,34,35 We used isoflurane for anesthetizing the rats during mPET imaging. There are many controversies regarding the relationship between isoflurane and brain function.…”
Section: Using Mpet To Determine How Mcs Changes the Brain Networkmentioning
confidence: 99%